(untitled) (Selecciones Matemáticas, 2023)
This article is the first part of one that has three parts. In the first one we present a vision of the evolution of the idea of integral, from ancient Greece to the Lebesgue integral. In the second part we will present how the Riemann integral has been investigated towards a unified theory of the integral.